Tuff, Flint, and Hazelnuts: Final Palaeolithic and Mesolithic Occupation at Netherhall Road, Maryport, Cumbria - Ann Clarke; Magnus Kirby (Internet Archaeology, 2022)
Evidence for Final Palaeolithic and Mesolithic occupation at Maryport, Cumbria, was discovered during the excavation of Roman occupation features by CFA Archaeology Ltd. A varied lithic assemblage was recovered including worked flint (55%) and tuff (43%), with the rest consisting of a small amount of chert, chalcedony, and rhyolite. Early occupation, probably dating to the Final Palaeolithic Federmesser-Gruppen, is demonstrated through different technological styles among the lithic assemblage. Three phases of activity were identified from cut features and there was a significant amount of charred hazelnut shell, which gave radiocarbon dates centring around 8200 cal BCE. This site provides the first clear evidence that tuff was exploited directly from sources in the Central Lake District, possibly as early as the Final Palaeolithic. The occupation evidence also demonstrates intensive processing of hazelnuts centring around 8200 cal BCE and lasting for 150–558 years. The dates and occupation span are almost identical to those derived from the Mesolithic structure at Cass ny Hawin 2 on the Isle of Man.